2014
DOI: 10.1371/journal.pone.0107909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Administration of Metronidazole or Prednisolone on Fecal Microbiota in Dogs

Abstract: Gastrointestinal microbiota have been implicated in the pathogenesis of various gastrointestinal disorders in dogs, including acute diarrhea and chronic enteropathy. Metronidazole and prednisolone are commonly prescribed for the treatment of these diseases; however, their effects on gastrointestinal microbiota have not been investigated. The objective of this study was to evaluate the effects of these drugs on the gastrointestinal microbiota of dogs. Metronidazole was administered twice daily at 12.5 mg/kg to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
102
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 67 publications
12
102
4
1
Order By: Relevance
“…All 250 bp pair-end sequence reads were connected using COPE software (Connecting Overlapped Pair-end, V 1.2.1) [27] to merge read pairs into tags from DNA fragments. Further data processing was performed as previously described [28–32,18] and included removal of sequencing noise using the pre.cluster tool in the MOTHUR software package v. 1.31.2 [33], and de novo chimera detection and removal in UCHIME v. 4.2. Operational taxonomic units (OTUs) were also determined using MOTHUR, with a 97% sequence identity threshold [33].…”
Section: Methodsmentioning
confidence: 99%
“…All 250 bp pair-end sequence reads were connected using COPE software (Connecting Overlapped Pair-end, V 1.2.1) [27] to merge read pairs into tags from DNA fragments. Further data processing was performed as previously described [28–32,18] and included removal of sequencing noise using the pre.cluster tool in the MOTHUR software package v. 1.31.2 [33], and de novo chimera detection and removal in UCHIME v. 4.2. Operational taxonomic units (OTUs) were also determined using MOTHUR, with a 97% sequence identity threshold [33].…”
Section: Methodsmentioning
confidence: 99%
“…Metronidazole is a nitroimidazole antibiotic and antiprotozoal that is commonly used in small animals with acute and chronic gastrointestinal disorders. A recent study in healthy dogs revealed that metronidazole decreases fecal bacterial diversity but increases the proportions of putatively beneficial bacteria such as Bifidobacterium . Tylosin is a macrolide antibiotic that is typically used to treat chronic enteropathies in dogs, especially a variant of antibiotic‐responsive diarrhea termed tylosin‐responsive diarrhea (TRD).…”
Section: Therapeutic Manipulation Of the Gastrointestinal Microbiomementioning
confidence: 99%
“…(Manchester et al 2019). Faecal bacterial diversity was also reduced when administering oral metronidazole for 14 days (12.5 mg/kg BID) to healthy dogs (Igarashi et al 2014). Similarly, oral administration of amoxicillin (10 mg/kg BID for 7 days) to healthy dogs resulted in differences in faecal bacterial composition before and after administration, with many faecal E. coli isolates showing increased resistance to multiple ABs during and after treatment (GrĂžnvold et al 2010).…”
Section: Effects Of Antibacterials On Gi Microbiotamentioning
confidence: 99%